Factors associated with initiation of pharmacological therapy and treatment changes in postural orthostatic tachycardia syndrome - Tidd, Samantha Jean Stallkamp; Zhang, Ryan X.; Cantrell, Christopher; Nowacki, Amy S.; Singh, Tamanna; Wilson, Robert (Frontiers in Neurology, 2024)
Purpose Postural Orthostatic Tachycardia Syndrome (POTS) is a heterogenous disorder of the autonomic nervous system that is often disabling. There are no FDA-approved therapies for the treatment of this condition. While some patients recover with baseline non-pharmacological intervention, others require repeated trials of off-label pharmacological therapies. The reasoning for this variable treatment response is unknown. The purpose of this work is to identify potential factors that are associated with higher odds of starting pharmacotherapy and/or a higher rate of POTS treatment changes. Methods Chart review of demographic, disease and treatment descriptions, medical history, and tilt table examinations of 322 POTS patients who were diagnosed between 2018 and 2020 at our tertiary care center was completed. We first identified the most significant factors associated with an increased odds of starting pharmacotherapy using variable selection techniques and logistic regression. We then identified the most significant factors associated with changes in POTS treatment strategies using variable selection techniques and negative binomial regression modeling. A significance level of 0.05 was utilized. Results A total of 752 POTS-specific treatment courses were cataloged, and 429 treatment changes were observed. The most cited reason for a change in management was uncontrolled symptoms. History of migraine headaches, reported fatigue, reported palpitations and a previous POTS diagnosis at an outside institution were found to be associated with a higher odds of starting pharmacotherapy for POTS symptoms (Odds Ratio of 2.40, 1.94, 2.62, 2.08, respectively). History of migraine headaches, reported fatigue, and higher heart rate differences on tilt table examination were found to be associated with an increase in the rate of POTS treatment changes (44, 66, 13% increase in incidence rate, respectively), while reported neck pain was associated with a decrease (27% decrease in incidence rate). Conclusion Our work identifies important areas of focus in the development of high-quality trials involving both the non-pharmacological and pharmacological treatment of POTS and highlights several characteristics of patients that may be more refractory to both baseline non-pharmacological treatments and current pharmacological treatment strategies.